EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATIC EDUCATION PADA PEMBELAJARAN MATERI SEGIEMPAT DI SMP NEGERI 6 PONTIANAK - Nihlah, Nihlah; R, Zubaidah; Mirza, Ade (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe current tendency of mathematics learning process still depended on teacher. Teacher domination in learning process cause passive students learning  activities and classically unreached KKM in school.The implementation of Realistic Mathematic Education Approach can be considered as a solution. This research aims to find out and describe the effectiveness of The effectiveness of Realistic Mathematics Education Approach in Rectangular Learning Material at SMPN 6 Pontianak. The method used in this research is descriptive method. The research subject was class VII D. The completeness of learning outcomes classically reached 67,74%, students’ learning activities during learning process was categorized active with the average percentage is 71,93% and teacher’s class management was categorized good with the average is 3,08. The conclusion that can be determine is Realistic Mathematics Education Approach in Rectangular Learning Material is noteffectiveto be applied in SMPN 6 Pontianak.Keywords: Effectivity,Approach, Realistic